2020
DOI: 10.21203/rs.3.rs-33957/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hygienic Sanitary Items Usage and Ovulatory Cycle Knowledge in India

Abstract: Background In India, most of the adolescent girls experience their first menstrual cycle with the lack of knowledge on menstruation, exacerbated by a plethora of taboos. Women undergoing menstruation experience discrimination, abuse, and neglect resulting from the myths and misconceptions built around menstruation. Such practices of discrimination and perpetuating myths might potentially lead to girls missing their schools and sometimes even dropping out after they start menstruating. NFHS-4 data shows that 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In India, it is found that most (89%) of adolescent girls (15)(16)(17)(18)(19)(20)(21)(22)(23)(24) years have incorrect knowledge of the ovulatory cycle and they are overwhelmed by many myths and misconceptions that lead them to endless suffering (Babbar and Saluja 2020). Bangladesh still has a lack of studies to uncover the issue properly.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In India, it is found that most (89%) of adolescent girls (15)(16)(17)(18)(19)(20)(21)(22)(23)(24) years have incorrect knowledge of the ovulatory cycle and they are overwhelmed by many myths and misconceptions that lead them to endless suffering (Babbar and Saluja 2020). Bangladesh still has a lack of studies to uncover the issue properly.…”
Section: Literature Reviewmentioning
confidence: 99%